2011
DOI: 10.1606/1044-3894.4135
|View full text |Cite
|
Sign up to set email alerts
|

Critical Issues for Psychiatric Medication Shared Decision Making with Youth and Families

Abstract: the primary aims of this article are to describe the current context for youth shared decision making (sDm) within the U.s. children's mental health system and to identify important considerations for the development of this approach as a research and service domain. the notion is substantiated in the literature that participation in treatment decisions can prepare youth for making their own decisions as adults, can be therapeutic, and can have positive effects on their self-confidence and self-esteem. still, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…There has been recent enthusiasm for the application of shared decision making (SDM) to the area of youth mental health, including depression . However, the rates of SDM in routine mental health care are likely to be low if adult data are any indication ,.…”
Section: Introductionmentioning
confidence: 99%
“…There has been recent enthusiasm for the application of shared decision making (SDM) to the area of youth mental health, including depression . However, the rates of SDM in routine mental health care are likely to be low if adult data are any indication ,.…”
Section: Introductionmentioning
confidence: 99%
“…Children in acute care settings, for instance, report feeling alienated when clinicians speak only to their parents and that a lack of communication is a barrier to SDM (Kelsey et al, 2007;O'Brien, Crickard, Rapp, Holmes, & McDonald, 2011). Studies in child mental health settings have found that interventions that include SDM reduce (child-reported) decisional conflict and improve treatment outcome, in terms of (child-reported) depression, quality of life, and satisfaction (Asarnow et al, 2009;Richardson, McCauley, & Katon, 2009;Westermann, Verheij, Winkens, Verhulst, & Van Oort, 2013).…”
mentioning
confidence: 99%
“…The Preparing for the Appointment (PFTA) worksheet was developed as part of a shared decision‐making model for youth and parents during psychiatric medication appointments (see Crickard, O'Brien, Rapp, & Holmes, ; O'Brien, Crickard, Rapp, Holmes, & McDonald, ). During development, parents and teens expressed a strong desire for a hands‐on tool they could use to help engage with one another and with their medication provider.…”
Section: Introductionmentioning
confidence: 99%
“…During development, parents and teens expressed a strong desire for a hands‐on tool they could use to help engage with one another and with their medication provider. Based on findings from several focus groups with teens, parents, and providers, the content of the PFTA worksheet was designed to capture not only what providers were interested in knowing for each appointment but also, more importantly, what parents and teens wanted to communicate (Crickard et al., ; O'Brien et al., ). The first part of the worksheet asks three questions about topics for today's appointment; the second section has four items asking about issues since the last appointment.…”
Section: Introductionmentioning
confidence: 99%